Analysis of School Administration Implementation - Ade Hermawan; Abd. Rohman; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2022)
Administrative order and regularity required because it is one of the important components for learning process. This study aimed to analyze the implementation of school administration tasks with evaluation method, which is a method that evaluated the success of implementing a program/activity. Data collection techniques used distributing questionnaires, observation, and documentation. Furthermore, the data were analyzed qualitatively. The results showed that the implementation of school administration in the areas of personnel administration, financial administration, infrastructure administration, public relations administration, archive administration, and student administration were in good category. Overall there are 67% of respondents who answered good administrative services, 31% answered quite well, and 2% answered less well. It can be concluded that the implementation of school administration work in general is good.